A membrane‐associated NAC domain transcription factor XVP interacts with TDIF co‐receptor and regulates vascular meristem activity. Issue 1 (5th December 2019) - Yang, Jung Hyun; Lee, Kwang‐Hee; Du, Qian; Yang, Shuo; Yuan, Bingjian; Qi, Liying; Wang, Huanzhong
Summary: Vascular stem cell maintenance is regulated by a peptide signaling involving Tracheary Element Differentiation Inhibitory Factor (TDIF) and Receptor TDR/PXY (Phloem intercalated with Xylem) and co‐receptor BAK1 (BRI1‐associated receptor kinase1). The regulatory mechanism of this signaling pathway is largely unknown despite its importance in stem cell maintenance in the vascular meristem. We report that activation of a NAC domain transcription factor XVP leads to precocious Xylem differentiation, disruption of Vascular Patterning, and reduced cell numbers in vascular bundles. We combined molecular and genetic studies to elucidate the biological functions of XVP. XVP is expressed in the cambium, localized on the plasma membrane and forms a complex with TDIF co‐receptors PXY‐BAK1. Simultaneous mutation of XVP and its close homologous NAC048 enhances TDIF signaling. In addition, genetics analysis indicated that XVP promotes xylem differentiation through a known master regulator VASCULAR‐RELATED NAC‐DOMAIN6 (VND6). Expression analyses indicate that XVP activates CLAVATA3/ESR (CLE)‐related protein 44 ( CLE44 ), the coding gene of TDIF, whereas TDIF represses XVP expression, suggesting a feedback mechanism. Therefore, XVP functions as a negative regulator of the TDIF‐PXY module and fine‐tunes TDIF signaling in vascular development. These results shed new light on the mechanism of vascular stem cell maintenance. Abstract : See also the Commentary on this article by Kucukoglu (2020), 226 : 5–7 .